(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This proverb concerns the field of formation of French and Uzbek folk proverbs. That is, the similarities and differences of folk proverbs for both sides are highlighted. From these proverbs, considered the spiritual heritage of every nation, exemplary examples in the direction of education are given. The Uzbek versions of French proverbs and their classification are clearly stated.